Counsellors' Viewpoint on the Need for a Hybrid Group Counselling Module on Stress, Resilience, and Personal Well-being for Trainee Teachers - Nurul Shuhada Sharif Mudin; Aslina Ahmad; Pau Kee (Peneliti.net, 2023)
This study explores public university counsellors’ perspectives on the need for a hybrid group counselling module addressing stress, resilience, and personal well-being for trainee teachers. A questionnaire was distributed to 32 counsellors, and the findings revealed that 88% of respondents expressed high agreement on the importance of developing such a module. The results show the necessity of structured interventions and support structures to address the well-being of trainee teachers and boost their performance. Finally, the findings of this research shed light on the significant role that counselling plays in promoting trainee teachers’ overall well-being. By addressing concerns with stress, resilience, and personal well-being, counsellors may significantly contribute to educators' general success and flourishing in training. This will lead to an improvement in educational quality and the development of a positive learning environment.